Mohs micrographic surgery for periocular skin tumours in Ireland. (November 2016) - Treacy, M.; Wynne, N.; Gale, J.; Duignan, E.; Moran, B.; Flynn, A.; Ormond, P.; Barry, R.; Khan, R.; Moriarty, P.; Cassidy, L.
Abstract Objective To describe the shared care and outcomes of patients with periocular skin tumours who underwent Mohs micrographic surgery (MMS) performed by dermatologists, followed by oculoplastic reconstruction undertaken by ophthalmologists at two teaching and one private hospital in Ireland. Research design and methods This was a retrospective chart review at the Royal Victoria Eye and Ear Hospital, St James Hospital and the Hermitage Clinic. Results One hundred and twenty seven patients had periocular Mohs surgery between November 2006 and January 2013 mainly indicated for basal cell carcinoma. The mean follow-up time was 2 years and to date there have been no local recurrences. Conclusions MMS is available in Ireland and should be considered for patients with facial tumours in the ocular region.